2016
DOI: 10.1063/1.4959075
|View full text |Cite
|
Sign up to set email alerts
|

A molecular dynamics study of dislocation density generation and plastic relaxation during shock of single crystal Cu

Abstract: The molecular dynamics simulation method is used to investigate the dependence of crystal orientation and shock wave strength on dislocation density evolution in single crystal Cu. Four different shock directions 〈100〉, 〈110〉, 〈111〉, and 〈321〉 are selected to study the role of crystal orientation on dislocation generation immediately behind the shock front and plastic relaxation as the system reaches the hydrostatic state. Dislocation density evolution is analyzed for particle velocities between the Hugoniot e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 42 publications
3
8
0
Order By: Relevance
“…It is also possible that the repulsive stress of dislocation‐dislocation interactions begins to saturate and balance the stress from the shock wave. It is worth noting that similar results have been observed in molecular dynamics simulations of dislocation development during the shock of copper single crystals (Sichani & Spearot, 2016). Copper crystals shocked parallel to {100} and {110} illustrate a large increase in dislocation density between 20 and 40 GPa shock pressure.…”
Section: Discussionsupporting
confidence: 81%
“…It is also possible that the repulsive stress of dislocation‐dislocation interactions begins to saturate and balance the stress from the shock wave. It is worth noting that similar results have been observed in molecular dynamics simulations of dislocation development during the shock of copper single crystals (Sichani & Spearot, 2016). Copper crystals shocked parallel to {100} and {110} illustrate a large increase in dislocation density between 20 and 40 GPa shock pressure.…”
Section: Discussionsupporting
confidence: 81%
“…The most naive approach to calculating the dislocation density would be to compute the total length of dislocation lines in a simulation box and divide by the box Accepted in Computational Materials Science [8] volume. This method was previously adapted in MD simulations [25] but a significant drawback of this approach is that one can only obtain a single value evolving with time, assuming the dislocation structure is homogeneous throughout the specimens. All local features are hence lost in the conversion process.…”
Section: Discrete To Continuum (D2c)mentioning
confidence: 99%
“…On the other hand, dislocation-based continuum models of plasticity are not restricted to the particular details of each dislocation, as they describe dislocations as continuous fields on different slip planes with some physical rules from length scales below the averaging volume size. In most cases, the way the continuum is related to the atomic scale is by transforming individual dislocations from the MD simulations into a total dislocation density field [9,25].…”
Section: Introductionmentioning
confidence: 99%
“…Complex phenomena can also arise; for example, a void can lead to highpressure phase transformation [4], and the barrierless melt nucleation will arise for some energetic nitramine [5]. However, numerous molecular dynamics (MD) simulations have demonstrated that the dislocation density will go up with the increase of impact pressure, while the nucleation and motion of dislocations still dominate the plastic deformation of the material under the high strain rate condition [6][7][8][9]. For example, when the strain rate is below 2.77 × 10 8 /s −1 and temperature is over 50 K, the plasticity is dislocation-mediated in the body-centered-cubic (BCC) metal tantalum [10].…”
Section: Introductionmentioning
confidence: 99%